OPTIMALISASI PENGGUNAAN FAKTOR PRODUKSI USAHATANI JAGUNG DI KABUPATEN BANYUMAS - Nurdiani, Ulfah; Prasetyo, Kunandar; Utami, Dewanti Risa (Universitas Galuh, 2023)
Maize has a fairly large level of need in Indonesia, namely 41% for food, 28% for feed, and 31% for other needs, such as seeds and scattered seeds. Sumbang Sub-District as a maize production center contributing 23.09 percent of the total harvested area in Banyumas Regency has a productivity level that is apparently lower than national productivity. Allocation of optimal production inputs can provide maximum productivity as well, which can increase profits for farmers. This study aims to determine the factors that affect corn production and the most optimal level of use of production inputs in corn farming in the corn production center area in Banyumas Regency. The site selection was carried out purposively in Sumbang District as the center of corn production in Banyumas Regency using the sampling method, namely nonpropotional quota sampling with a sample of 50 corn farmer respondents. The data analysis method used in this study is to use the Cobb-douglass frontier stochastic production function to determine the production factors that affect corn production, namely land area, seeds, labor, organic fertilizers, urea fertilizers, phonska fertilizers, pesticides and herbicides. This study provides results that production inputs that have a real influence on corn production in the production center of Banyumas Regency are land area, seeds, organic fertilizers, urea fertilizers and pesticides with the achievement of possible optimization, namely increasing the use of land area, seeds, labor, organic fertilizers and herbicides accompanied by the use of optimal production inputs according to the dosage recommended by the Ministry of Agriculture.